5 questions on the principles of DevOps - Allen, Courtney (O'Reilly Media, 2017)
"Five Questions is a series where we sit down with leading industry practitioners and ask them for real-world stories and examples of how they're using technology in their everyday work. In this interview, Courtney Allen talks with Lisa Phillips about how an organization can implement the core principles of DevOps, tips for overcoming challenges, and tools to consider when making the shift."--Resource description page